Typifications of the Linnaean names Carduus eriophorus, Carduus eriophorus var. spurius, and Cnicus ferox (Asteraceae) - Del Guacchio, Emanuele; Iamonico, Duilio (Phytotaxa, 2015)
Two specimens from the Linnaeus Herbarium (at LINN) and an illustration by Bauhin & Cherler are designated as the lectotypes of, respectively, Carduus eriophorus (≡ Cirsium eriophorum), Carduus eriophorus var. spurius [= Cirsium × gerhardtii, syn. nov. (Cirsium vulgare × Cirsium eriophorum)], and Cnicus ferox (≡ Cirsium ferox). All the taxa involved in this study belong to Cirsium sect. Eriolepis.